Made poorer by choice: Worker outcomes in social security vs. private retirement accounts - Ahmed, Javed; Barber, Brad M.; Odean, Terrance (Journal of Banking & Finance, 2018)
Can the freedom to choose how retirement funds are invested leave workers worse off? Via simulation, we document that choice in stock v. bond allocation and type of equity investments in private accounts leads to lower utility and greater risk of income shortfalls relative to private accounts without choice. We also compare private account outcomes to currently promised Social Security benefits to demonstrate that a representative worker (an average wage earner) benefits more from private-account alternatives—with or without choice—than do most workers. Thus, representative worker outcome should not be used to assess population-wide benefits of private account alternatives.